Demand for money : an analysis of the long-run behavior of the velocity of circulation - Bordo, Michael D.; Jonung, Lars. (New Brunswick [New Jersey] : Transaction Publishers, 2004)
The book proposes that institutional factors as opposed to real income, play a greater role in velocity than previously thought. As matter of fact, institutional factors have a major impact on monetary policy.
Rev. ed. of: The long-run behavior of the velocity of circulation / Michael D. Bordo, Lars Jonung. c1987.
Includes bibliographical references and index.
opc 27/10/16
Loans
Keywords: Circular velocity of money - econometeric models; Demand for money; Money supply